Pembelajaran Berdiferensiasi: Analisis Kritis terhadap Konsepsi Pembelajaran Berdiferensiasi dan Praktiknya di Indonesia - Fauziah, Zumrotul; Khoiriyah, Siti (Universitas Negeri Padang, 2024)
The curriculum must be able to accommodate the needs and characteristics of students. The new curriculum in Indonesia called the Merdeka Curriculum, advises teachers to implement differentiated learning. This research analyses the concept and practice of differentiated learning in Indonesia. The method used in this research is a Systematic Literature Review (SLR). Data sources were taken from Scopus and Google Scholar to search for literature regarding the conception of differentiated instruction and the practice of differentiated learning in Indonesia. The results show that the concept of differentiated learning is to give different treatment to students based on their needs and learning styles. Differentiated learning is divided into process, content, product and learning environment. Differentiated learning has been practised in some schools in Indonesia by teacher movers, but mostly in primary schools and inclusive schools. The reason is that many teachers in Indonesia still need to gain the knowledge and competence to implement differentiated learning in their classrooms. Therefore, this research will help teachers in Indonesia understand more about the concept of differentiated learning and adopt the best practices in their classrooms